Inspection of facades with Unmanned Aerial Vehicles (UAV): an exploratory study - Ballesteros Ruiz, Ramiro Daniel; Lordsleem Júnior, Alberto Casado; Aquino Rocha, Joaquin Humberto (Revista ALCONPAT, 2021)
The objective of this study was to evaluate the use of Unmanned Aerial Vehicles (UAVs) as a visual tool for the inspection of pathological manifestations in facades, through an exploratory study. Currently, the relevance of UAVsis growing as a new mechanism for obtaining data and visual inspection of buildings, optimizing time. The research strategy had three distinct steps: a literature review, an experimental procedure, and data processing, aiming to verify the viability of the inspection procedure. There is evidence of the convenience of UAV use, particularly where access is difficult, which reduces time and cost, generates greater security, and allows 3D reconstruction of the building under inspection, generating more accurate diagnoses.